EUROPEAN REALISM AND CRITICAL REALISM - Sattorova Guliniso Foziljon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
This article is about realism and critical realism and researching information about this period. Realism was a literary movement that began in the mid-19th century and can be defined as a move against Romanticism that stressed truthful and relatable, also realistic, subject matter. Critical Realism is a branch of philosophy that distinguishes between the 'real' world and the 'observable' world. The 'real' can not be observed and exists independent from human perceptions, theories, and constructions.